Effect Of Work Ethos On Organizational Commitments And Its Impact On Employees Performance Of Forestry Office Of North Kalimatan Province - achmad daengs gs (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Destination: to analyze and prove the effect of work ethic on organizational commitment and its impact on employee performance. This type of research is included in explanatory research or explanatory research. The population in this study were all employees atNorth Kalimantan Forest Service Design / methodology / approach: The data analysis technique used in this study is a path analysis approach. Findings:The results showed that partially work ethic has a significant effect on employee performance with the assumption that organizational commitment is considered constant. In addition, the results of this study also indicate that partially work ethic has a significant effect on employee organizational commitment. Then partially organizational commitment has a significant effect on employee performance with the assumption that the work ethic variable is considered constant. Furthermore, a simultaneous test was carried out where the results of this study showed that work ethic and organizational commitment together had a significant effect on employee performance. Organizational commitment is able to mediate the effect of work ethic on employee performance. Practical implications: Intensifying work ethic towards organizational commitment and its impact on the performance of forestry service employees Paper type: Research paper Keywords: Work Ethic, Organizational Commitment, Employee Performance